The most frequent cause of 90‐day unplanned hospital readmission following colorectal cancer resection is chemotherapy complications. (September 2015) - Ang, C. W.; Seretis, C.; Wanigasooriya, K.; Mahadik, Y.; Singh, J.; Chapman, M. A. S.
Abstract Aim NHS England deems 90‐day readmission rates as a marker of quality of care. The causes of readmission have not been previously reported in the UK. The aim of this study was to examine the factors associated with 90‐day readmission following colorectal cancer surgery at a hospital trust with a catchment population 1.2 million. Method A retrospective review was performed of all patients undergoing resection for colorectal cancer between January 2012 and December 2013. Unplanned readmission was defined as an emergency admission to the trust for any cause within 90 days of surgery. Readmission analyses were restricted to patients discharged from hospital within 28 days of resection. Results A total of 570 patients underwent surgery, of whom 522 were discharged within 28 days and are included for readmission analysis. The readmission rate was 24.3% (127 patients with a total of 163 episodes of hospital readmissions) within 90 days following surgery. The most frequent cause for readmission was complications related to adjuvant chemotherapy (18.4%) followed by wound‐related complications (14.1%). Most patients presenting with wound‐related complications were admitted within 60 days and patients with chemotherapy‐related complications after 61 days; 13/127 (10.2%) patients who were readmitted underwent emergency surgery, and one patient died following readmission. Multivariate analysis demonstrated that comorbidity was the only independent risk factor. Conclusion Ninety‐day readmissions include a high number of readmissions secondary to chemotherapy‐related complications, whereas most surgical‐related readmission present within 60 days.